OP0151 The 6-Minute Walk Test Assessed in Juvenile Dermatomyositis After Long Term Follow-Up: The Impact of Muscle, Lung, and Heart Dysfunction. (9th June 2015) - Berntsen, K.S.; Tollisen, A.; Schwartz, T.; Kirkhus, E.; Aaløkken, T.M.; Lund, M.B.; Flatø, B.; Sjaastad, I.; Sanner, H.
Abstract : Background: Juvenile dermatomyositis (JDM) is a rare idiopathic inflammatory myositis of childhood affecting mainly the skin and proximal striated muscle. The heart and lungs may also be involved, albeit often subclinically. The 6-minute walk test (6-MWT) is a well-established, low cost tool in the functional assessment of pulmonary and cardiovascular disease (1). It has never been systematically assessed in JDM. Objectives: To compare the 6-MWT in JDM patients with that of age- and gender-matched controls from the general population, and to explore the contribution of striated muscle-, heart- and lung function to the results. Methods: 58 Norwegian JDM patients (mean age 25.2 (12.5) years, 61% female) were clinically examined mean 16.9 (10.6) years after symptom onset and compared with 59 healthy age- and gender matched controls. All participants performed a 6-MWT according to a standard procedure. The distance walked (in meter) was recorded for each person. Muscle function was assessed by the manual muscle test (MMT-8) and the childhood myositis assessment scale (CMAS); heart function by echocardiography; and lung function by spirometry, diffusing capacity for carbon monoxide (DLCO) and body plethysmography. Thoracic HRCT was performed in patients only. All participants completed the short form 36 (SF-36) and a questionnaire about the frequency of physical exercise. In patients, disease activity was measured by the disease activity score (DAS) and disease damage by myositis damage index (MDI). Inactive disease was defined according to the Printo criteria. Results: The distance covered in the 6MWT was shorter in patients than controls; 593 (81) and 649 (79) meters respectively (p<0.001). There was no difference in height between the two groups. Patients with active disease walked shorter than patients with inactive disease; 562 (75) and 622 (76) meters respectively (p=0.004). CMAS, MMT-8, physical activity frequency, HRCT findings, height, and DLCO (alveolar volume- and Hb corrected) showed, in descending order, the strongest correlations with the 6MWT (table 1 ). There was no correlation between cardiac function and the 6MWT. Performing multivariate linear regression analysis, height, CMAS, HRCT findings, physical activity and DLCO were associated with the distance walked in the 6MWT, adjusted R square 0.53 (table 1 ). Conclusions: The 6MWT was significantly lower in patients than controls. Apart from general factors such as height and physical activity frequency, our study indicates that muscle dysfunction, but also lung impairment, affect the 6MWT in JDM patients. References: ATS statement: guidelines for the six-minute walk test. American journal of respiratory and critical care medicine. 2002;166(1):111-7. Disclosure of Interest: None declared